(untitled) (Andamios, Revista de Investigación Social, 2016)
In the present article, Fatema Mernissi reflects on globalisation, specifically on the historically troubled relationship between the muslim world and west. To do so, she analyzes elements such as flight, migration, the night and the moon, searching in these (other) spaces the possible grounds of secular western world’s fear of Islam.